Degradation of Endogenous and Exogenous Genes of Genetically Modified Rice with Cry1Ab during Food Processing. Issue 5 (23rd April 2014) - Zhang, Wei; Xing, Fuguo; Selvaraj, Jonathan Nimal; Liu, Yang
Abstract In order to assess the degradation of endogenous and exogenous genes during food processing, genetically modified rice with Cry1Ab was used as raw material to produce 4 processed foods: steamed rice, rice noodles, rice crackers, and sweet rice wine. The results showed various processing procedures caused different degrees of degradation of both endogenous and exogenous genes. During the processing of steamed rice and rice noodles, the procedures were so mild that only genes larger than 1500 bp were degraded, and no degradation of NOS terminator and Hpt gene was detected. For rice crackers, frying was the most severe procedure, followed by microwaving, baking, boiling, 1st drying, and 2nd drying. For sweet rice wine, fermentation had more impact on degradation of genes than the other processing procedures. All procedures in this study did not lead to degradation of genes to below 200 bp, except for NOS terminator. In the case of stability of the genes studied during processing of rice crackers and sweet rice wine, SPS gene was the most, followed by the Cry1Ab gene, Hpt gene, Pubi promoter, and NOS terminator. Practical Application In our study, we gained some information about the degradation of endogenous and exogenous genes during 4 foods processing, compared the different stabilities between endogenous and exogenous genes, and analyzed different effects of procedure on degradation of genes. In addition, the fragments of endogenous and exogenous genes about 200 bp could be detected in final products, except NOS terminator. As a result, we provided some base information about risk assessment of genetically modified (GM) food and appropriate length of fragment to detect GM component in processed foods.